VI Konferencja ICLARS “Human Dignity, Law, and Religious Diversity: Designing the Future of Inter-Cultural Societies”, Kordoba (Hiszpania), 19-21 września 2022 r. - Stanisz, Piotr (Studia z Prawa Wyznaniowego, 2022)
Sprawozdanie z VI Konferencji ICLARS “Human Dignity, Law, and Religious Diversity: Designing the Future of Inter-Cultural Societies”, Kordoba (Hiszpania), 19-21 września 2022 r.